1988
DOI: 10.1103/physrevb.37.6731
|View full text |Cite
|
Sign up to set email alerts
|

Shakeup in soft-x-ray emission. I. The low-energy tail

Abstract: The I.soft-x-ray emission spectra for Al and Si, and the E emission for graphite and diamond are analyzed, taking into account the efFects of multielectron transitions which produce a low-energy tail on the main band. Through an appropriate transformation on the initial states, it is shown that the Anal-state rule of Yon Barth and Grossman is a direct result of exchange. A "Pauli rigidity" forces the initial-state wave function to approach that of the Snal state, except near the Fermi energy. An assumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…16 Spectral features of SXE spectra are very similar to those of the spectra which were already measured by several authors. 5,6,[17][18][19][20] These structures have been well elucidated by the total DOS. The two strong structures at around h SXE ϭ90.2 and 92.5 eV have been assigned to the high DOS around L 2 Ј ; and L 1 bands.…”
Section: Resultsmentioning
confidence: 92%
“…16 Spectral features of SXE spectra are very similar to those of the spectra which were already measured by several authors. 5,6,[17][18][19][20] These structures have been well elucidated by the total DOS. The two strong structures at around h SXE ϭ90.2 and 92.5 eV have been assigned to the high DOS around L 2 Ј ; and L 1 bands.…”
Section: Resultsmentioning
confidence: 92%
“…The low-energy tailing of the spectrum is believed to be caused by the finite lifetime of the valence holes and the weak low-energy hump is associated with multiple electron excitations accompanying the filling of the core hole. 16 As is seen in Fig. 1, the SXE is substantially dependent on the excitation energy when it is tuned below 144 eV.…”
mentioning
confidence: 75%
“…It has long been suggested that there is a final state rule for core-hole band spectral shapes ͑XAS, XES, and Auger͒ and an initial state rule for intensities in spectra from simple metals. [47][48][49][50][51] This has been applied and tested in several cases of sp bonding, including simple metals, 50-53 silicon, 54 and graphite. 11 For Si there is little to argue against a true core-hole-induced bound state at the L 2,3 edge, or for other semiconductors and other core thresholds ͑see references in Ref.…”
Section: General Aspects Of Core-hole Perturbationsmentioning
confidence: 99%